2018
DOI: 10.1089/ars.2016.6911
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Circadian Period, But Not Phase and Amplitude, Is Robust Against Redox and Metabolic Perturbations

Abstract: Aims: Circadian rhythms permeate all levels of biology to temporally regulate cell and whole-body physiology, although the cell-autonomous mechanism that confers ∼24-h periodicity is incompletely understood. Reports describing circadian oscillations of over-oxidized peroxiredoxin abundance have suggested that redox signaling plays an important role in the timekeeping mechanism. Here, we tested the functional contribution that redox state and primary metabolism make to mammalian cellular timekeeping.Results: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 83 publications
5
62
0
Order By: Relevance
“…As the dilution rate and/or the glucose concentration decreases the period of oscillation becomes progressively longer and the fraction of unbudded cells increases (Beuse et al., ; Chin et al., ; Slavov & Botstein, ). This may be similar to glucose‐dependent effects on daily cycles that occur in fibroblasts, and U2OS cells and in strains of Neurospora that have lost metabolic compensation (Lamia et al., ; Putker et al., ; Sancar, Sancar, & Brunner, ). During LOC, glucose‐limited cells accumulate carbohydrates in the form of trehalose and glycogen (Ouyang, Xu, Mitsui, Motizuki, & Xu, ; Wang et al., ; Xu & Tsurugi, , ).…”
Section: Characteristics Of Metabolic Rhythmsmentioning
confidence: 65%
See 1 more Smart Citation
“…As the dilution rate and/or the glucose concentration decreases the period of oscillation becomes progressively longer and the fraction of unbudded cells increases (Beuse et al., ; Chin et al., ; Slavov & Botstein, ). This may be similar to glucose‐dependent effects on daily cycles that occur in fibroblasts, and U2OS cells and in strains of Neurospora that have lost metabolic compensation (Lamia et al., ; Putker et al., ; Sancar, Sancar, & Brunner, ). During LOC, glucose‐limited cells accumulate carbohydrates in the form of trehalose and glycogen (Ouyang, Xu, Mitsui, Motizuki, & Xu, ; Wang et al., ; Xu & Tsurugi, , ).…”
Section: Characteristics Of Metabolic Rhythmsmentioning
confidence: 65%
“…This process forms a critical part of the oscillation and populations deleted for glucose‐6‐phosphate dehydrogenase initiate cycling, but the oscillation stalls the first time it reaches LOC (Tu et al., , ). Genetic and pharmacological inhibition of the pentose phosphate pathway significantly affects circadian gene expression rhythms in mouse fibroblasts (Putker et al., ).…”
Section: Characteristics Of Metabolic Rhythmsmentioning
confidence: 99%
“…Over- and hyper-peroxidation rhythms of peroxiredoxins have been found in human red blood cells [25], which have no nucleus that are found to be driven by hemoglobin auto-oxidation rhythms and are associated with the degradation of hyperoxidized peroxiredoxins [26]. Inhibiting the pentose phosphate pathway, a critical source for NADPH, was found to influence circadian rhythms in cells across species [27], with a recent study showing an effect on the amplitude and phase of the clock [28] This work further supports a feedback from cellular energy metabolism to the transcriptional/translational circadian clock.…”
Section: Cellular Energy Is Circadianmentioning
confidence: 99%
“…The redox state of the cell in turn can directly affect the function of some clock proteins (e.g., Rev‐Erbα) (Hirano et al., ; Rey et al., ; Wende et al., ). In addition, oxidative damage of clock proteins may enhance their degradation (e.g., PER2) or hinder their function, and oxidative stress has been shown to shift mammalian clocks through apoptosis signaling‐related kinase, a member of the MAPKKK (MAPKK kinase) family or the antioxidant transcription factor, NRF2 (nuclear factor E2‐like 2) (Imamura et al., ; Putker et al., ; Tamaru et al., ; Wible et al., ). It is still unclear how such effects on the core molecular clock are important for adjusting other processes to the metabolic state of the cell(s).…”
Section: Introductionmentioning
confidence: 99%
“…It is still unclear how such effects on the core molecular clock are important for adjusting other processes to the metabolic state of the cell(s). Nonetheless, one important clock function may be to coordinate enzymatic removal of ROS in anticipation of peak oxidative stress (Nagy & Reddy, ; Putker et al., ). Interestingly, the removal of ROS and cellular redox reactions involves redox recycling of antioxidant enzymes and molecules, (Kinoshita, Aoyama, & Nakaki, ; Nagy & Reddy, ), and studies using mature red blood cells have demonstrated circadian oscillations in the redox states of antioxidant enzymes in the absence of transcription/translation feedback loops (Cho, Yoon, Kim, Woo, & Rhee, ; Homma et al., ; O'Neill & Reddy, ).…”
Section: Introductionmentioning
confidence: 99%